(untitled) (Jurnal Bahasa, 2023)
This study pursues the field of phonology to examine a dialect that has never received attention from outside researchers, namely the Midai Malay dialect (DMM). DMM is a dialect spoken in Midai Island, Natuna Regency, Indonesia. The study was conducted to identify and analyze the phoneme inventory based on the structural approach pioneered by Ferdinand de Saussure. In order to make the study successful, interviews were held using Morris Swadesh’s 230 Word List, which was modified based on the Nusantara situation to interview informants. The findings of the study show that DMM has seven vowel phonemes, consisting of the vowels /i/, /e/, /a/, /e/, /u/, /o/, dan / /. There are four types of diphthong vowel phonemes in DMM, namely /-ai/, /-ui/, /-au/ and /-oi/. In addition, the analysis of consonant phonemes found that there are 21 consonants in DMM. The analysis of the phoneme inventory is a good exposure of DMM that has never been explored by academics. So, it is hoped that the linguistic study of DMM will be continued so that the dialect’s features can be shown. Keywords: Phoneme inventory, Malay Midai dialect, structural analysis, phonology, Morris Swadesh word list, Ferdinand de Saussure approach Full text: PDF